-3(2n-1)=-(7+7n)

Simple and best practice solution for -3(2n-1)=-(7+7n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2n-1)=-(7+7n) equation:


-3(2n-1)=-(7+7n)

We simplify the equation to the form, which is simple to understand
-3(2n-1)=-(7+7n)

Reorder the terms in parentheses
+(-6n+3)=-(7+7n)

Remove unnecessary parentheses
-6n+3=-(+7+7n+)

Remove unnecessary parentheses
-6n+3=-7-7n

We move all terms containing n to the left and all other terms to the right.
-6n+7n=-7-3

We simplify left and right side of the equation.
+1n=-10

We divide both sides of the equation by 1 to get n.
n=-10

See similar equations:

| 7+w=45.75 | | 2n+30=12n | | 63=7(2a+7) | | 5(a+5)-3=3(2-a) | | 5-8y+5x/3=4 | | 3+4n=35 | | 2t-4=-8 | | 60x^3+116x^2-56x= | | 4/9+1/5+n | | 84=6(4-5n) | | 5-(x-6)=7 | | -7q+8=-29 | | 84=6(4-5) | | -6=(-4x-8) | | x-5y=1004 | | -6(3n+2)+3n=-4(n+1)-3n | | 6x+4=32+2x | | 2+-4=8 | | x/5+3=-17 | | z-14=38 | | 2/3=4/5+c | | 20=-.09x+109 | | 1+2k=4-2k+5k | | 10.50+h=147 | | -0.08t^2+4.48=0 | | 4x+-1=4x+7 | | 8y-70=2 | | -6x+5=-4-3x | | -4p+3p=3p-1-5-6 | | 8+3X6/2 | | x=1/4+1/4 | | 7-x=3+5 |

Equations solver categories